PENGARUH FREE CASH FLOW DALAM MEMPREDIKSI LABA DAN ARUS KAS OPERASI MASA MENDATANG - Sari Bujana, Ni Komang Ayunda; Yaniartha, Putu D'yan (E-Jurnal Akuntansi, 2015)
Earnings and operating cash flows are an indicator to measure the performance of entity. While, Free cash flows will describe the ability of entity in the future. This research aimed to examine the effect of free cash flows in predicting future earnings and future operating cash flows. The sample of this research is public company listed in Indonesia Stock Exchange year 2009 to2013. The data is analyzed by using simple linier regression. The result of this research finds that positive free cash flows have the ability to predict future earnings and future operating cash flows. This research give an insight that the higher free cash flow earned by an entity, the higher earning and operating cash flows in the future.
Keywords: free cash flows, earnings, and future operating cash flows